2015
DOI: 10.5194/tc-9-2101-2015
|View full text |Cite
|
Sign up to set email alerts
|

Microwave scattering coefficient of snow in MEMLS and DMRT-ML revisited: the relevance of sticky hard spheres and tomography-based estimates of stickiness

Abstract: Abstract. The description of snow microstructure in microwave models is often simplified to facilitate electromagnetic calculations. Within dense media radiative transfer (DMRT), the microstructure is commonly described by sticky hard spheres (SHS). An objective mapping of real snow onto SHS is however missing which prevents measured input parameters from being used for DMRT. In contrast, the microwave emission model of layered snowpacks (MEMLS) employs a conceptually different approach, based on the twopoint … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 50 publications
5
32
0
Order By: Relevance
“…This implies that the present dielectric model and the thermal conductivity model from Löwe et al (2013) are based on exactly the same microstructural parameters. In light of recent attempts to unify microstructural descriptions of snow for microwave modeling (Löwe and Picard, 2015), we also note that the MG formula (Eq. 6a) can be likewise obtained as the lowfrequency limit of the quasi-crystalline approximation for aligned spheroids (Ao and Kong, 2002).…”
Section: Series Expansion Of Permittivity Via Correlation Functions: mentioning
confidence: 99%
“…This implies that the present dielectric model and the thermal conductivity model from Löwe et al (2013) are based on exactly the same microstructural parameters. In light of recent attempts to unify microstructural descriptions of snow for microwave modeling (Löwe and Picard, 2015), we also note that the MG formula (Eq. 6a) can be likewise obtained as the lowfrequency limit of the quasi-crystalline approximation for aligned spheroids (Ao and Kong, 2002).…”
Section: Series Expansion Of Permittivity Via Correlation Functions: mentioning
confidence: 99%
“…Two constant values were considered here: extremely cohesive or less sticky particles. Löwe and Picard (2015) have made progress in understanding stickiness from micro-CT data. There are theoretical limits, based on snow density (Löwe and Picard, 2015, Eqs.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst Löwe and Picard (2015) have shown that it may be possible to determine stickiness from micro-CT measurements of the snow, an appropriate value of stickiness is not known for the field observations used in this paper. Roy et al (2013) and Löwe and Picard (2015) showed that non-sticky representation in DMRT-ML is inappropriate.…”
Section: Dmrt-mlmentioning
confidence: 99%
See 2 more Smart Citations